Energy efficiency of a house in Mediterranean region: insulation and glazing impact - Salaheddine Jaouaf; Bourassia Bensaad; Abdelhakim Dorbane (The Journal of Engineering and Exact Sciences)
The insulation of a building's envelope is critical for reducing energy consumption, enhancing indoor thermal comfort, and achieving sustainable development goals. This theoretical work focused on the energy and thermal aspect of insulators and glazing to determine the optimal thermal insulation and the best glazing for the building envelope in the Mediterranean region where the province of Ain Temouchent, Algeria, was taken in this study. This study evaluated the effectiveness of insulation materials, which are expanded polystyrene, glass wool, rock wool, and wood fiber of varying thicknesses, and glazing in the Algerian market. The TRNSYS 17 software is used to simulate the building's behavior. The study finds that wood fiber insulation with a 9 cm thickness provides the best thermal performance, resulting in a 26% reduction in energy costs compared to 3cm of expanded polystyrene. Furthermore, upgrading from single to double glazing can reduce heating and cooling costs by 23% and 10%, respectively, demonstrating the importance of proper insulation and glazing in achieving energy efficiency, and enhancing indoor thermal comfort for occupants. In conclusion, this study provides valuable findings for designing energy-efficient buildings with optimal thermal insulation and glazing. Future research should explore broader factors affecting building performance, such as the long-term performance and durability of materials in varying climates and building designs, as well as the impact of occupancy and building orientation. Although the study acknowledges its limited examination of factors and options, it still provides valuable insights into building performance with insulation and glazing.